Pengaruh Asia Sustainability Reporting Rating dan ASEAN Corporate Governance Scorecard Terhadap Firm Value - Bella Rahmadhani Anggita Putri; Dwi Jayanti (Owner : Riset dan Jurnal Akuntansi, 2025)
This study aims to analyze and determine the effect of the Asia Sustainability Reporting Rating and ASEAN Corporate Governance Scorecard on firm value. The objects in this study are 6 companies that get the rating category in Asia Sustainability Reporting Rating for the period 2019 to 2023. The research uses a quantitative approach with panel data analyzed as pooled data. The sample technique in this study was purposive sampling, obtained 30 sample data using multiple linear regression analysis. Data obtained from the NCCR website and the company's annual report. The results based on partial tests show that the Asia Sustainability Reporting Rating has no effect on firm value and the ASEAN Corporate Governance Scorecard has no effect on firm value. While the simultaneous test shows that the Asia Sustainability Reporting Rating and ASEAN Corporate Governance Scorecard have an effect on firm value as proxied by PBV. The implications of this study emphasizes the impoetance of a holistic approach in the implementation of Environmental Social Governance aspects to improve market perception and firm value.